Reflections on the threshold for PM2.5 explosive growth in the cumulative stage of winter heavy aerosol pollution episodes (HPEs) in Beijing - Junting Zhong; Xiaoye Zhang; Yaqiang Wang (Tellus: Series B, Chemical and Physical Meteorology, 2019)
Particulate matter smaller than 2.5 μm in diameters (PM2.5) often experiences explosive growth (mass concentration at least doubled in several to 10 h) in winter aerosol pollution episodes (HPEs) in Beijing. Whether a threshold value exists for such PM2.5 explosive growth is uncertain. Here, we used PM2.5 mass concentration, surface and vertical meteorological factors including winds, temperature, relative humidity (RH), and radiation in winter (Jan., Feb., and Dec.) from 2013 to 2017 to confirm the existence of the threshold for PM2.5 explosive growth and determine the threshold value. We found that the positive feedback from aerosols to near-ground radiative cooling to anomalous inversion is effectively triggered under slight or calm winds when the near-ground PM2.5 mass reaches a certain threshold. A threshold value for PM2.5 explosive growth (100 μg m−3) is determined by analyzing 30 cumulative stages (CSs) during 28 HPEs. Keeping the PM2.5 mass concentration transported from the south of Beijing below this value would avoid the majority of PM2.5 explosive growth during the 30 CSs. As a reference for the government to further set the emission reduction target, a more stringent threshold value (∼71 μg m−3) is established by differentiating the lighter HPEs from the heavier HPEs.